Ekspresi Cathepsin-D Lebih Tinggi pada Adenokarsinoma Folikuler Tiroid Dibandingkan Adenoma Folikuler Tiroid - Agusry Yakob; Salmiah Agus (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2015)
Type of thyroid follicular neoplasms are benign thyroid disorders such as follicular adenomas (AK) and malignant form of follicular adenocarcinoma (AKF). Both of these morphological types of neoplasms are difficult to distinguish, because it has a similiar picture. The criteria used to distinguish these two lesions in the infiltration of tumor cells into the capsule in follicular adenocarcinoma. Cathepsin-D is one of the useful biological marker lysis of extracellular matrix including tissue capsule at the time of invasion. Histological markers can be used as an indicator for the assessment of tumor cell invasion into capsule. This study aims to determine whether there are differences and relationships cathepsin-D expression in thyroid follicular neoplasms to help properly diagnosis. Methods The design of analytic observational study with cross sectional approach. The study population was derived from paraffin blocks that have been diagnosed as follicular carcinoma and adenoma in the Anatomical Pathology Laboratory of the Faculty of Medicine, University of Andalas in 2010 to 2012. Obtained sample size formula based on 32 samples. The sampling method proportional stratified random sampling with thyroid follicular adenoma 13 cases and 19 cases of thyroid follicular adenocarcinoma. In the samples examined using immunohisto-chemistry mouse monoclonal antibody cathepsin-D. The data obtained were analyzed with the chi-square test. Results In epidemiology of thyroid disorders such as thyroid neoplasms benign or malignant more common in women than in men, while age is incidence of reproductive age, 33-55 years. Of the 32 samples, thyroid follicular adenoma (n=13) and follicular thyroid adenocarcinoma (n=19) showed expression of cathepsin-D were higher in follicular thyroid adenocarcinoma (84.2%) compared with follicular adenoma (15.8%). Statistically using Chi square test found a significant relationship between the expression of cathepsin-D with the type of follicular thyroid neoplasma with a value of p